Anthropomorphism of Animal Images at the Turn of the 19th — 20th Centuries: Taxidermy, Book Illustration, Postcards - Yurgeneva, A.L. (Художественная культура, 2025)
The article analyses anthropomorphic images of animals at the turn of the 19th and 20th centuries. The relevance of this research is determined by the attention of various scientific disciplines to the problem of human-animal interaction, as well as by the abundance of images of animals endowed with anthropomorphic features in the modern visual culture (primarily the Internet space). As part of the study, it was concluded that during the period under review, such images acquired new features and went beyond the realm of satire. That process took place against the background of the formation of ecological thinking and the flourishing of the art of taxidermy as a scientific method. One of the new trends was the creation of human-like groups of animals, the plot for which was based on fabliau, folk children’s songs, and scenes of everyday life. The conducted analysis allowed establishing the mutual influence of literature and taxidermy. The author concludes that the success of anthropomorphic biological groups led to changes in the nature of children’s book illustration. Artists began to create images of animals having psychological insight, existing in an elaborately depicted household environment. Gradually, they moved away from the literary basis: what became the main subject of the image was the surrounding everyday reality populated by ‘civilized’ animals. Updated anthropomorphic animals filled periodicals and postcards.